2019
DOI: 10.1109/tasc.2019.2900556
|View full text |Cite
|
Sign up to set email alerts
|

The 16 T Dipole Development Program for FCC and HE-LHC

Abstract: A future circular collider (FCC) with a center-ofmass energy of 100 TeV and a circumference of around 100 km, or an energy upgrade of the LHC (HE-LHC) to 27 TeV require bending magnets providing 16 T in a 50-mm aperture. Several development programs for these magnets, based on Nb 3 Sn technology, are being pursued in Europe and in the U.S. In these programs, cos-theta, block-type, common-coil, and canted-costheta magnets are ex-plored; first model magnets are under manufacture; limits on con-ductor stress leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Further studies have shown that yoke size and inter-beam distance have a great influence in field quality, because the cross-talk between the two apertures induces systematic multipoles extremely difficult to correct, especially b 2 and b 3 . In particular, it resulted that b 2 component was not acceptable for an accelerator magnet field quality (b 2 variation > 40 units), therefore some design parameters were modified to meet the requirements, which are summarized in Table I [6], [7]: the inter-beam distance and the iron yoke diameter have been increased respectively to 250 mm and 660 mm, in order to reduce as much as possible the cross-talk effect [9]. Furthermore, for mechanical purpose the iron yoke is enclosed in an Al alloy shell 50 mm thick to provide the additional and final pre-stress in coils during cool down and everything is bound together by a steel shell 20 mm thick which works as vessel.…”
Section: A Design Parametersmentioning
confidence: 99%
“…Further studies have shown that yoke size and inter-beam distance have a great influence in field quality, because the cross-talk between the two apertures induces systematic multipoles extremely difficult to correct, especially b 2 and b 3 . In particular, it resulted that b 2 component was not acceptable for an accelerator magnet field quality (b 2 variation > 40 units), therefore some design parameters were modified to meet the requirements, which are summarized in Table I [6], [7]: the inter-beam distance and the iron yoke diameter have been increased respectively to 250 mm and 660 mm, in order to reduce as much as possible the cross-talk effect [9]. Furthermore, for mechanical purpose the iron yoke is enclosed in an Al alloy shell 50 mm thick to provide the additional and final pre-stress in coils during cool down and everything is bound together by a steel shell 20 mm thick which works as vessel.…”
Section: A Design Parametersmentioning
confidence: 99%
“…The design options explored within the EuroCirCol initiative (Schoerling et al 2019) show that, by using a conductor with the FCC target performance, the maximum stress in the conductor reaches values in the range of 150 MPa during magnet assembly and of 200 MPa during operation at cold.…”
Section: Structural Parametersmentioning
confidence: 99%
“…These magnets struggle with the quench phenomenon, which is a sudden and local Figure 1 Cross-section of cos-theta magnet for FCC and HE-LHC. A stack of three Rutherford cables is highlighted in red [13] transition from the superconducting to the normal state [4]. Quenches emerge randomly during continuous operation.…”
Section: Introductionmentioning
confidence: 99%
“…Next, an adaptive resolution strategy is discussed for the spectral method. Lastly, the methods are compared and employed to compute the heat conduction in a benchmark model representing a superconducting Rutherford cable as used in superconducting accelerator magnets [13,14], see Fig. 1.…”
Section: Introductionmentioning
confidence: 99%